Characterization Of Hydrophobic Seaweed Film Reinforced With Kenaf Bast Cellulose Nanofibers - Che Ismail, Che Mohamad Hazwan (2022)
Plastics are durable and resistant to biodegradation processes in the natural environment. Intensive researches have been conducted in past to develop the film from the natural source. The seaweed-based film showed excellent functional properties, so there is a need to investigate its performance and impact on surroundings to determine its longevity and harmfulness. Using kenaf nanocellulose as filler reinforcement is well known to increase the mechanical properties of films. The hydrophilicity nature of the seaweed can be countered by silane treatment using triethoxymethyl silane to give hydrophobicity properties to the film. The nanocellulose based seaweed film were prepared using solvent casting process. In this research project, study on physicochemical properties of the biodegradable film and its performance has been completed. This study include the understanding of the mechanical, physical, chemical, thermal, morphology, biodegradability, and hydrophilicity properties of the film. Detail study has been carried out to identify the optimum measure of silane surface treatment on seaweed films hydrophobicity. Different amounts of nanocellulose incorporated within the seaweed film also has been studied and compared to one another. The rate of water interaction with the seaweed films were measure by calculate the weight increase with respect to time.